How ethical leadership promotes employee well-being at work: mediating role of leadermember exchange and organizational identification - Silva, V. H.; Duarte, A.P.; Simões, E.; Neves, J. (5th Symposium on Ethics and Social Responsibility Research, 2019)
Previous research points to the existence of a positive relationship between the exercise of ethical leadership and the promotion of several positive employee job attitudes and behaviors. Following this research line, the present study sought to analyze how ethical leadership relates to the affective well-being of subordinates. Well-being refers to a combination of arousal and pleasure at work (Warr, 1990) and can be influence by ethical leaders behavior notably because these tend to defend their subordinates, to protect them from unfairness, and to mobilize the necessary job-related resources (Kalshoven & Boon, 2012). Since these behaviors increase the degree to which leaders develop high-quality relationships with followers (Bedi, Alpaslan, & Green, 2016; Niemeyer & Cavazotte, 2016), leader-member exchange (LMX) has been proposed as a psychosocial mediator between ethical leadership and several follower outcomes (e.g., Chughtai, 2016; Engelbrecht, Heine, & Mahembe, 2017; Kalshoven, Den Hartog, & De Hoogh, 2011). Additionally, since ethical leaders are more trustworthy they should promote organizational identification (Tyler, Boeckmann, Smith, & Huo, 1997), this construct being also related to higher affective wellbeing at work. Therefore, this research tested a model proposing that ethical leadership predicts followers’ affective well-being through the mediating effect of LMX and organizational identification. Data were gathered from a sample of 273 employees from different organizations by means of an electronic survey that included measures selected from the relevant literature. Several analyses were conducted using AMOS and the macro Process (Hayes, 2012) for IBM SPSS. The results reveal that ethical leadership is significantly correlated with LMX, organizational identification, and job-related affective well-being. More importantly, the results showed that ethical leadership predicts followers’ affective well-being and that this effect is totally mediated by the quality of leader-follower relationships and followers’ identification with the company. The model explained about 50% of the variance in affective well-being. Practical implications of the overall results for the enhancement of employee well-being at work are discussed.